IMPROVING THE METHODOLOGY OF USING MOBILE EDUCATIONAL TECHNOLOGIES IN "INFORMATICS AND INFORMATION TECHNOLOGIES" IN GENERAL EDUCATION SCHOOLS - Akmaljon Azizjon Mamasoliyev (Galaxy International Interdisciplinary Research Journal, 2023)
The focuses on improving the methodology of using mobile educational technologies in "Informatics and Information Technologies" in general education schools, specifically for 6th grade students. The goal is to enhance the teaching and learning experience by leveraging mobile technologies. The study aims to develop and implement a new approach that maximizes the benefits of mobile educational technologies in the classroom. By integrating these technologies into the curriculum, educators can engage students in interactive learning experiences that promote active participation and knowledge retention. The abstract highlights the importance of adapting teaching methods to meet the needs of the digital generation and emphasizes the potential of mobile technologies in enhancing educational outcomes